A experiência de uma clínica forasteira - Perrella, Ana Carolina (2019)
This paper investigates the performance of a clinic outside the traditional clinical setting and open to the pulse of the city, from the apparatus Clinical Care and Psychoanalysis on Roosevelt Square, to think an outsider clinic. To that end, we are interested to note a zone of intersection between the experience of the Xingu (Amazônia) and the Roosevelt Square, emphasizing the singularities of each practice. The study emphasizes the operation of both apparatus, bringing elements of clinical activity held in each of them. In order to understand these outsiders do experiments, refers to the etymology of the word stranger, extracting its meaning both directions, namely, “out of the office boundaries” and “alien, outside.” What is noticeable, in both experiments, is that the city is made up and intervenes in the clinical space in different ways. A bet that is made in this study is at a clinic that opens at random, the risks and uncertainties of urban life, capable of producing displacements in the territories of living, both the patient and the clinician